Designing JUMPISA: A PISA-Based Jumping Task to Support Students’ Statistical Literacy using Jambi Context - Duano Sapta Nusantara; Florante P. Ibarra; Feri Tiona Pasaribu; Uci Lusinda (Pendidikan Matematika STKIP Kusuma Negara, 2025)
Statistical literacy is a critical competence for 21st-century students, yet many struggle to apply statistical concepts in authentic contexts. This study reports the development of JUMPISA, a PISA-based Jumping Task contextualized for secondary students in Jambi Province, designed to enhance students’ abilities to interpret, represent, and reason with data. Employing a design research approach with iterative development, the study included preliminary and formative evaluations to assess task validity and feasibility. The JUMPISA tasks integrate content on uncertainty, work-related contexts, and varying reasoning levels in line with PISA’s framework. Results indicate that students demonstrated notable improvement in engaging with authentic statistical problems. Beyond practical effectiveness, this study advances the theoretical understanding of context-sensitive PISA Task design, showing how locally contextualized, inquiry-driven tasks can be systematically developed and validated for international assessment. JUMPISA exemplifies a model for aligning global assessment frameworks with local educational contexts, offering guidance for both researchers and practitioners in designing assessment-informed instructional activities.